PENINGKATAN KEMAMPUAN CREATIVE PROBLEM SOLVING MATEMATIS SISWA SMP DENGAN PENDEKATAN CHALLENGE BASED LEARNING (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2016)
This study examined students' mathematical achievements and creative problem solving (CPS) enhancement in overall and according to gender. Samples are eighth grade students in one of secondary school in Bandung Regency. Experiment class received challenge based learning (CBL) approach while control class received scientific approach. The instrument used was mathematical CPS ability test. The collected data were then statistically analyzed. The results showed that mathematical CPS achivement and enhancement in students who received CBL learning approach is better than students who received scientific approach both for male (p= 0.001; p
Keywords: Challenge Based Learning; Creative Problem Solving Matematis; Perbedaan Gender; Mathematical Creative Problem Solving; Gender Difference